Roughness of two simultaneous harmonic complex tones in various pitch registers - SZCZEPAŃSKA-ANTOSIK, Joanna (Archives of Acoustics, 2008)
The purpose of the study was to determine the dependence of perceived roughness on the frequency ratio of two simultaneous harmonic complex tones. A set of 36 dyads forming musical intervals of various tuning systems was presented in three pitch registers. Twelve sound engineering students judged each dyad for roughness by the method of absolute magnitude estimation. Results show that roughness considerably varies with the frequency ratio of the two complex tones, what is a well-known phenomenon. A new finding, being in contrast to published theories of roughness, is that some of the equally-tempered intervals are perceived less rough than their counterparts based on integer frequency ratios. This effect is attributed to slow beats that arise between the harmonics of two complex tones when the frequency ratio of the tones slightly departs from the integer ratio.